Mechanism of Hybrid Reinforcement and its Effect on some Properties of Binary Polymer Blend - Awham M. Hameed; Entihaa G. Daway (Engineering and Technology Journal, 2014)
The aim of current study is carrying out some modifying in properties of resin material (Unsaturated polyester, UPE) by adding thermoplastic material (polystyrene, PS) with different weight ratios included (0%, 5%, 10%, 15% and 20%) of (PS) to prepare binary polymer blend. The optimum ratio was selected in terms of the homogeneity case between the two polymers and studying the nature of the surfaces of the prepared materials using the optical microscope. Some mechanical tests were performed to determine the values of impact strength (I.S), ultimate tensile strength (UTS) for all prepared specimens. The ratio (80/20, weight/weight)% of (UPE/PS) blend was selected and reinforced with fibers volume fraction Фf = 10% using three types of fibers included (glass fibers (G.F), Carbon fibers (C.F) and hybrid from the two types (5% G.F and 5% C.F). All the above tests were repeated after the reinforcement for comparing the results and studying the behavior of materials under work. The results exhibited that the values of (I.S) increase with increasing of the blending ratio of (PS) while the values of (UTS) decrease at blending ratios (10, 15) % of (PS) and return to increase at the ratio 20% . After the reinforcement, it was found that the composite reinforced with carbon fibers records the highest values of impact strength for un notch specimens while the hybrid composite has the highest value of the ultimate tensile strength comparing with E-glass and carbon fibers composites.